EDUKASI DAN PENDAMPINGAN TEKNOLOGI BUDIDAYA PISANG HASIL IN VITRO PADA MASYARAKAT DESA HUTAN DI KABUPATEN LUMAJANG - Erfan Dani Septia; Maftuchah Maftuchah; Aulia Zakia (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Indonesia is a country that is in a strategic position, so it has a high potential to develop horticultural subsectors, one of which is banana commodities. According to data from BPS, there are three provinces in Indonesia with the most banana production, including East Java, Lampung, and West Java. East Java Province produced 2,059,923 tons, followed by Lampung Province with 1,438,559 tons, and West Java Province with 1,125,899 tons. Banana is one type of tropical fruit that is commonly found in Indonesia. The various types of bananas known include Raja bananas, Mas Bananas, Cavendish, Barangan, Kepok, etc. The availability of several types of bananas is constrained due to limited supply. One of the crucial factors in banana development is the availability of healthy and uniform seeds in adequate quantities. The availability of healthy banana seeds is very vital. The way that can be taken to obtain healthy banana seedlings in large amounts is through tissue culture methods. So far, the production of banana seedlings has been hampered by the low level of plantlet multiplication and the high percentage of browning, which causes the death of explants in the initiation phase. In addition, obtaining ready-to-plant banana seedlings usually takes many stages of subculture, thus requiring a lot of time and resources. In vitro plant culture is a method of taking certain plant parts (isolation) to be used as planting material grown under aseptic conditions (free from contaminants) and in a controlled environment. This can be an effective method for the mass propagation of bananas in Indonesia. The utilization of forest land and forest village communities are natural resources and human resources that have the potential to develop this banana commodity. For this reason, it is necessary to provide technical assistance for banana cultivation to the community, especially forest village communities. Through this program, it is hoped that the downstream procedures for planting bananas from in vitro cultures can be widely known and implemented by the local community as a solution to overcoming the problem of the availability of banana seeds during banana cultivation. The service activity begins with discussion and consolidation to identify banana farmers' real issues in Lumajang.